Central Asian Prism of The Belt and Road Initiative: Social Sustainability and Capacity Building Specifics - Javohir Masharipov; Ulugbek Khasanov (Journal of Central Asian Studies)
As traditional international institutions decline in effectiveness, states increasingly adopt pragmatic, interest-driven foreign policies. Nowhere is this shift more evident than in Central Asia, where historical legacies, geographic constraints, and economic imperatives necessitate adaptive strategies. This article explores how Central Asian states are redefining their national development and foreign policies amid shifting global dynamics, with a focus on China’s Belt and Road Initiative (BRI). It argues that BRI participation enables infrastructure development, industrial diversification, and job creation while reinforcing regional cooperation. Ultimately, the findings demonstrate that BRI engagement helps these states enhance their geopolitical balancing strategies and assert agency in an increasingly multipolar world.